DEVELOPMENT OF STATE CIVIL APPARATUS (ASN) COMPETENCE OF BAPPEDALITBANG OF KUTAI BARAT REGENCY - Imelda Turisna Mariana Joka; Dandan Haryono; Irwan Waris (RADJA PUBLIKA, 2025)
This study aims to analyze the competency development of State Civil Apparatus (ASN) in the Regional Development Planning, Research, and Development Agency (BappedaLitbang) of West Kutai Regency. The focus of the study is directed at three main indicators, namely competency development planning, implementation of competency development, and competency development evaluation . This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation analysis. Research informants consist of structural officials, functional officials, and implementing staff within the BappedaLitbang environment selected by purposive sampling technique. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, while data validity testing used triangulation of sources, methods, and member checks. The results of the study indicate that ASN competency development planning in BappedaLitbang West Kutai is not fully based on job analysis and is still constrained by budget constraints. At the implementation stage, the implementation of the training program is not optimal, with only 27% of ASN participating in training according to job requirements, far below the target of 68%. Furthermore, the available training is more general in nature and less relevant to the demands of post-equivalency functional positions. At the evaluation stage, competency development program assessments are still administrative in nature and do not measure the training's impact on performance. This research emphasizes the need for a more contextual, systematic, and sustainable ASN competency development strategy to improve the effectiveness of regional development planning.